2020
DOI: 10.1111/jonm.12911
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of thriving: Mindfulness and contextual performance among Turkish nurses

Abstract: Aims To examine the role of thriving in the relationship between mindfulness and contextual performance. Background Thriving has been known as one of the most important components in the professional development of nurses. Previous studies have also shown that mindfulness and contextual performance have an effective role in workplace. Yet, we still know relatively little about the underlying mechanisms that explain the relationship among mindfulness, thriving and contextual performance in a nursing context. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 63 publications
2
18
0
4
Order By: Relevance
“…Similarly, recovery can originate within the person, as well as triggered by the environment. Recovery can be a behavior when doing mindfulness practices [108,109] or recovery during work can be initiated by the employer, for example by offering mindfulness interventions [89,110]. From a medical point of view, when activated by internal or external triggers, psychological strain can arise caused by hormonal chemical activation, having psychological and physical consequences [111].…”
Section: Factors That Moderate and Mediate Personal Energy At Workmentioning
confidence: 99%
“…Similarly, recovery can originate within the person, as well as triggered by the environment. Recovery can be a behavior when doing mindfulness practices [108,109] or recovery during work can be initiated by the employer, for example by offering mindfulness interventions [89,110]. From a medical point of view, when activated by internal or external triggers, psychological strain can arise caused by hormonal chemical activation, having psychological and physical consequences [111].…”
Section: Factors That Moderate and Mediate Personal Energy At Workmentioning
confidence: 99%
“…El desempeño contextual, tal como lo mencionan Bilal et al (2015) y Kalia y Bhardwaj (2019), ocupa un papel importante en el estudio de la psicología y el comportamiento organizacional, pues enfoca su valoración a la disposición positiva y voluntaria que tiene el empleado para contribuir al cumplimiento de las funciones organizacionales más allá de su puesto de trabajo, aun cuando estas resulten personalmente complejas por desarrollar (Han et al, 2015). En sí, la esencia central de este constructo consiste en la idea de prosperar conjuntamente a nivel individual y organizacional, producto de las estrechas relaciones interpersonales forjadas entre los miembros de la institución (Sahin, et al, 2020).…”
Section: Fundamento Teóricounclassified
“…En conclusión, el constructo del desempeño contextual presenta evidencia importante del amplio alcance que poseen los componentes que agrupan su valoración, así mismo, existe literatura científica que afirma existe un impacto significativo entre estos factores y los resultados obtenidos por la organización. Por ejemplo, en el sector salud y educación, estudios previos han confirmado la relación positiva que existe entre el desempeño contextual y variables como la comunicación, la autoeficiencia del personal, el optimismo, compromiso, rendimiento y desarrollo sostenido de la institución (Aboagye et al, 2020;Bilal et al, 2015;Delgado et al, 2018;Flores, 2017;Palenzuela et al, 2019;Rodríguez, et al, 2018;Sahin, et al, 2020;Vilcamichi, 2017). Por ello, es que se recomienda fomentar comportamientos de desempeño contextual al interior de este tipo de organizaciones, en beneficio de la calidad de los servicios que se ofrecen a la sociedad (Malik, 2018), hallazgo en el que se basa el presente estudio y del cual deriva el objetivo de investigación.…”
Section: Fundamento Teóricounclassified
See 1 more Smart Citation
“…In this respect, mindfulness can be associated with thriving. Although many studies have indicated a relationship between mindfulness and thriving in various samples (workers, nurses) (Allen & Kiburz, 2012;Baer & Lykins, 2011;Brown & Ryan, 2003;Siegel, 2007;Şahin, Arıcı Özcan, & Arslan Babal, 2020), only a few studies (Tan & Martin, 2015;Warren, 2016) have looked at the relationship between mindfulness and thriving among adolescents. To bridge this gap, the current study aimed to examine the relationship between mindfulness practices and thriving in a sample of adolescents.…”
Section: Introductionmentioning
confidence: 99%